ประสิทธิผลของการใช้โปรแกรมการเสริมสร้างพลังอำนาจในการฟื้นฟูสมรรถภาพปอดสำหรับผู้ที่เป็นโรคปอดอุดกั้นเรื้อรัง โรงพยาบาลเชียงดาว จังหวัดเชียงใหม่ - นางจิรารัชต์ คำใจ (เชียงใหม่ : บัณฑิตวิทยาลัย มหาวิทยาลัยเชียงใหม่, 2020)
Chronic obstructive pulmonary disease (COPD), is a disease causing obstruction of the airway and which adversely affect the respiratory system and the other organs. Pulmonary rehabilitation can slow the progression of the disease, and patients’ adherence to pulmonary rehabilitation is essential for improving their care outcome. This operational study aimed to verify the effectiveness of implementing the Empowerment Program Pulmonary Rehabilitation for persons with COPD (EPPR) developed by Kumjai, Srisaard and Ngamchen (2012). The study was conducted at a community hospital in Chiang Mai province from April to August 2014. The study participants composed of 213 persons with COPD, 147 before program implementation and 66 after program implementation. The framework of implementing evidence proposed by the National Health and Medical Research Council of Australia (National Health and Medical Research Council [NHMRC], 1999) was used as the framework of program implementation for this study. Patient behavior and health service utilization were evaluated for outcome of program implementation. Data were analyzed by using descriptive statistics. The study results revealed that: 1. The percentage of study participants who showed good practice of pulmonary rehabilitation was 48.29% and 89.39% for before and after EPPR implementation respectively. 2. The percentage of study participants who utilized health services due to dyspnea exacerbation for before and after the EPPR implementation was 44.90% and 84.84%, respectively. The findings of this study confirm the effectiveness of implementing the EPPR in terms of improving behavior for lung rehabilitation among people with COPD. The researcher recommends long term implementation of EPPR to ensure sustainability of the outcomes. Further study should be conducted in order to test other outcome.